1996
DOI: 10.1007/bf03172725
|View full text |Cite
|
Sign up to set email alerts
|

Child care in the preschool years: Attachment, behaviour problems and cognitive development

Abstract: The possible implications ofthe experience ofnon parental care on cognitive development and on behaviour problems are considered in interaction with individual and contextual variables. A sample of 47 Swiss children who experienced varying kinds of care arrangements were studied longitudinally between 1 and 5 years ofage. The effects of the experience of care were related to mothers' reports of behavioral problems (CBCL, with subscales of internalizing and of externalizing problems) at age 5, and to cognitive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 17 publications
0
29
0
3
Order By: Relevance
“…Pierrehumbert, Ramstein, Karmaniola, and Halfon (1996) found no evidence for an independent relationship between amount of childcare and problem behaviour at age 5; rather, the relationship was mediated by attachment to the mother. Type of care mattered: Collective care was related to higher externalizing behaviour than family-based care.…”
mentioning
confidence: 57%
“…Pierrehumbert, Ramstein, Karmaniola, and Halfon (1996) found no evidence for an independent relationship between amount of childcare and problem behaviour at age 5; rather, the relationship was mediated by attachment to the mother. Type of care mattered: Collective care was related to higher externalizing behaviour than family-based care.…”
mentioning
confidence: 57%
“…First, in a crosssectional study (n ϭ 94 mother-child dyads), Crockenberg and Litman (1991) found that toddlers from low-socioeconomic status (SES) families whose mothers were employed (which was virtually equivalent with NMC) were less defiant than their low-SES peers whose mothers were not employed. Second, Pierrehumbert, Ramstein, Karmaniola, and Halfon (1996) found that extensive day care involvement (at least 2 days per week during the preschool years) protected insecurely attached children (n ϭ 47) against the risk for disruptive behavior at 5 years old.…”
Section: The Effects Of Child Care Type May Depend On the Level Of Rimentioning
confidence: 99%
“…Information about the SES was collected at the NICU discharge, with a scale based on the Hollinghead's Index, combining parents education level and work position (Pierrehumbert, Ramstein, Karmaniola, & Halfon, 1996).…”
Section: Participantsmentioning
confidence: 99%